Comparative study of effects of ramosetron and ondansetron on global satisfaction of patients on cisplatin chemotherapy in head and neck cancers - Srivastava, Swapnil; Ahmed, Quazi Shahir; Sayedda, Kauser (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To compare level of satisfaction of the patients receiving ramosetron and ondansetron in prevention of acute and delayed nausea and vomiting associated with cisplatin chemotherapy. Methods: 60 patients were recruited in the study. Patients were randomly allocated to ramosetron (R) and ondansetron group (O). Patients were screened between day 1 and day 7. Study visits included clinic visits on day 8, day 9 and day 14. Patient diaries were used to record patients’ global satisfaction which was based on severity of nausea and vomiting using visual analogue scale (VAS), recorded daily until day 12 starting from day 8. On 14th day the patient diary cards were collected back. Results: VAS score was significantly lower in R group (46.2±4.95) as compared to O group (63.7±5.06) (p<0.01) in acute phase of nausea and vomiting indicating level of satisfaction higher in R group. Similarly, in delayed and overall phase R group (49.57±14.63 and 48.9±12.91 respectively) experienced lower range of scoring on VAS scale as compared to O group (63.0±8.49 and 63.10±7.38 respectively). The difference was statistically significant (p<0.01). Conclusions: Level of overall satisfaction of the patients in R group was significantly higher as compared to O group in patients receiving the two drugs for prevention of nausea and vomiting caused by cisplatin chemotherapy in head and neck cancer patients.